Co-design of the agroecological transition path for the Fatick department - Piraux, Marc; Belmin, Raphaë; Ndour, Moussa; Fall, Modou Gueye; Mbaye, Banna; Bayo, Finda; Ba, Marième; Dione, Geneviève; Mané, Cherif; Diallo, Ibrahima; Kouakou, Patrice; Lairez, Juliette; et al. (2024)
The Agroecology Initiative supports local agroecological transitions through a Living Landscape Agroecology (ALL) approach. In Senegal, this initiative is active in the department of Fatick through a local dynamic called DYTAEL (Dynamique pour une Transition AgroEcologique locale), which started in 2021. The report summarizes a workshop held by DyTAEL in collaboration with CIRAD and ISRA to co-construct an agroecological transition path in the Fatick department.